A new synchrotron rapid‐scanning X‐ray fluorescence (SRS‐XRF) imaging station at SSRL beamline 6‐2. (6th September 2018) - Edwards, Nicholas P.; Webb, Samuel M.; Krest, Courtney M.; van Campen, Douglas; Manning, Phillip L.; Wogelius, Roy A.; Bergmann, Uwe
Abstract : A new large‐range rapid‐scan X‐ray fluorescence (XRF) imaging station at the Stanford Synchrotron Radiation Lightsource is described. This station uses a continuous rapid‐scan system with a scan range of 1000 × 600 mm and a load capacity of up to 25 kg, capable of 25–100 µm precision for elemental XRF mapping and X‐ray absorption spectroscopy of a wide range of objects. Abstract : This paper describes a new large‐range rapid‐scan X‐ray fluorescence (XRF) imaging station at beamline 6‐2 at the Stanford Synchrotron Radiation Lightsource at SLAC National Accelerator Laboratory. This station uses a continuous rapid‐scan system with a scan range of 1000 × 600 mm and a load capacity of up to 25 kg, capable of 25–100 µm resolution elemental XRF mapping and X‐ray absorption spectroscopy (XAS) of a wide range of objects. XRF is measured using a four‐element Hitachi Vortex ME4 silicon drift detector coupled to a Quantum Detectors Xspress3 multi‐channel analyzer system. A custom system allows the X‐ray spot size to be changed quickly and easily via pinholes ranging from 25 to 100 µm, and the use of a poly‐capillary or axially symmetric achromatic optic may achieve a <10 µm resolution in the future. The instrument is located at wiggler beamline 6‐2 which has an energy range of 2.1–17 keV, creating K emission for elements up to strontium, and L or M emission for all other elements. XAS can also be performed at selected sample positions within the same experiment, allowing for a more detailed chemical characterization of the elements of interest. Furthermore, sparse excitation energy XRF imaging can be performed over a wide range of incident X‐ray energies. User friendliness has been emphasized in all stages of the experiment, including versatile sample mounts, He purged chambers for low‐ Z analyses, and intuitive visualization hardware and software. The station provides analysis capabilities for a wide range of materials and research fields including biological, chemical, environmental and materials science, paleontology, geology and cultural heritage.